2024
DOI: 10.1038/s41531-023-00623-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with age at onset of Parkinson’s disease in the UK Biobank

Yuanfeng Huang,
Qian Chen,
Zheng Wang
et al.

Abstract: Substantial evidence shown that the age at onset (AAO) of Parkinson’s disease (PD) is a major determinant of clinical heterogeneity. However, the mechanisms underlying heterogeneity in the AAO remain unclear. To investigate the risk factors with the AAO of PD, a total of 3156 patients with PD from the UK Biobank were included in this study. We evaluated the effects of polygenic risk scores (PRS), nongenetic risk factors, and their interaction on the AAO using Mann–Whitney U tests and regression analyses. We fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The possibility of an interaction between PGS and lifestyle factors cannot be entirely ruled out. In fact, an interaction between PGS and smoking was reported in two recent studies 6,7 . In our study, we found a three times higher expected hazard of PD in the subgroup of participants that used no protective lifestyle factor and had a high PGS as compared to patients with a low PGS.…”
Section: Discussionmentioning
confidence: 84%
“…The possibility of an interaction between PGS and lifestyle factors cannot be entirely ruled out. In fact, an interaction between PGS and smoking was reported in two recent studies 6,7 . In our study, we found a three times higher expected hazard of PD in the subgroup of participants that used no protective lifestyle factor and had a high PGS as compared to patients with a low PGS.…”
Section: Discussionmentioning
confidence: 84%
“…Although the original study included some demographic and socioeconomic variables, they missed the important lifestyle factors, such as coffee and tea intake. Previous studies found that tea and coffee intake were inversely associated the PD 7 10 . Using directed acyclic graphs (DAGs) to illustrate potential biases and confounding factors would aid in better understanding the relationship between physical activity and PD.…”
mentioning
confidence: 90%